Is er minder tussen ons? Over religie en homosexualiteit. - De Haene, Piet; Lapauw, Stefaan; Marivoet, Frank; Roegiers, Jan; Weekers, Bert (Antwerpen : FWH, 1981)
Fonds Suzan Daniel (FSD)
Nederlands
Monografie